FSM-based conformance testing methods: A survey annotated with experimental evaluation; Information and Software Technology; Vol. 52, iss. 12 - Dorofeeva M. Yu. Margarita Yurievna; El-Fakih Kh. Khaled; Maag S. Stephane; Cavalli A. R. Ana; Yevtushenko N. Nina (2010, 2010)
Title screen